Aspects of comorbidity in children with COVID-19 - V. V. Shkarin; O. V. Kovalishena; A. V. Sergeeva; А. А. Murtayeva (LLC "Diagnostics and Vaccines", 2023)
Numerous literature data and our observations testify to the widespread permanent growth of combined infections, especially new ones, as well as combined infectious diseases with somatic ones. This is a new scientific direction in medicine, which we have designated as «complex comorbidity», and which can be considered as one of the main trends in the evolution of infectious pathology in general. The article presents an analysis of scientific articles on comorbidity with COVID-19 in children, taking into account clinical and epidemiological features in the pandemic (2020-2021) and pre-pandemic (2015-2019) periods. It has been estab- lished that the emergence of a new subtype of coronavirus at the end of 2019. An unfavorable epidemiological situation for seasonal coronavirus infection preceded by a pronounced trend towards an increase in the proportion of cases of diseases associated with coronavirus from 10.5% in the 2014-2015 epidemic season. up to 32.8% in the 2018-2019 season. The pandemic period was characterized by a lower susceptibility of children compared to adults, as well as a high proportion of «asymptomatic» and mild forms of infection. In turn, in the pre-pandemic period, «seasonal» coronaviruses preferred to infect, for the most part, precisely children's contingents with moderate onset of the disease.